Juridical Review on Asset Management of Land Rights for Roe Building Which Has Run Out Time (Analysis Decision Dispute in PT. Citra Mandiri, Central Java) - Hemastuti Arini; Misbakhul Munir; Djauhari Djauhari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
In this study will be discussed how the consideration of judges in deciding this case and land management measures HGB assets. This research is an analytical description with normative juridical approach, by studying library materials (literature study) that the data used is secondary data, which includes the primary legal materials, secondary, and tertiary. The judges consider that the vulnerable period from 2009 to 2016 the land was returned to state control because certificate of HGB have expired in 2009 and was not renewed due to the occurrence of the land dispute. So PT CMJT and occupants of the home office, the same is not so entitled to the house. But in 2015, PT CMJT has committed an unlawful act that is with noticeboards statement of ownership and forcible emptying of the occupants of the house. Then the judges ruled on compensation of 100 million rupiah to PT CMJT the residents were harmed. This can be avoided if the PT CMJT have a good asset management can be done through asset management, namely certification, storage, security,Keywords: Asset Management; Regional Enterprise; Land Broking.